Frequency and classification of neoplasms in the male reproductive tract of dogs, histopathologically diagnosed in the Animal Pathology Laboratory of the Universidad Nacional Mayor de San Marcos. Period: 2011-2017 - Ortiz O., Laura (2020)
This study aimed to carry out a retrospective study of the cases of neoplasms in the male reproductive tract in dogs that have been diagnosed by histopathology in the laboratory of animal pathology of the Faculty of Veterinary Medicine of the National University of San Marcos (Lima, Peru) during the period 2011-2017. A total of 85 cases of neoplasms were diagnosed in the reproductive system of 1096 cases of canine neoplasms (7.75%). The most frequent were the testicular tumours (43.5%), the most common being the diffuse seminoma.